Pengembangan Bahan Ajar Kajian Fisika Sekolah Menengah Berbasis Proyek Untuk Meningkatkan Penguasaan Konsep Fisika Calon Guru - Sutrio Sutrio; Joni Rokhmat; Satutik Rahayu (Prodi Fisika FKIP Unram, 2021)
The objectives of this study is to develop project-based Physics Study teaching materials for Middle School that can improve concept mastery of high school teacher candidates. This research includes education development divided into three steps i.e the preliminary study, the product design development, and the product testing. The results showed that the developed instructional materials were suitable for use in learning and fulfilled the validation test by experts for the components of content feasibility, presentation and language in a good category. The responses of the student after using the teaching materials are very good for supporting and completing teaching materials during lectures. The tested teaching materials of Physics learning in Middle School can improve mastery of high school physics concepts for teacher candidates.Keywords: project-based teaching materials, school physics studies, mastery of physics concepts